Student Course Registration Coordination System (Scrcs) - Song, Wang Ye (Universiti Malaysia Sarawak (UNIMAS), 2023)
Nowadays, the Universiti Malaysia Sarawak (UNIMAS) online course registration system has been developed to be user-friendly and easy to choose the course for registration instead of having to fill up paper-based registration forms manually in order to register for the courses. However, for new students who are still very new to the Unimas online course registration system’s process and procedure, they could face issues or problems while carrying out online course registration such as website errors, quota full, unable to choose the course mentioned in the guidebook for that semester, functionality errors, course time clashes with other registered courses, technical errors, etc. Therefore, Student Course Registration Coordination System has been proposed to solve this issue. There will be a chat box that enables students to interact with the lecturer in charge to solve their issues in a shorter time.